The Impact of Aerobic Exercise on Mood Symptoms in Trauma-Exposed Young Adults: A Pilot Study - Mizzi, Allison L.; McKinnon, Margaret C.; Becker, Suzanna (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Physical activity has beneficial effects on mood in both healthy and clinical populations. Emerging literature suggests that physical activity may benefit psychological symptoms, such as depressive mood, in those with post-traumatic stress disorder (PTSD). It is estimated that 76% of Canadians have experienced a traumatic event during their lifetime (Van Ameringen et al., 2008). Thus, there is a large proportion of the population that does not meet criteria for PTSD but may still suffer from trauma-related symptoms such as depression and require support for their mental health. The current pilot study aimed to evaluate the impact of an aerobic exercise intervention on mood symptoms in trauma-exposed young adults. Methods: Twenty-five low active young adults with subclinical trauma symptoms but no current or past diagnosis of PTSD were recruited. Participants were randomly assigned to participate in an eight-week exercise intervention group or a waitlist control group. Mood symptoms were assessed before and after the intervention. In addition, measures of aerobic fitness, trauma symptoms, emotion regulation, and trait mindfulness were assessed at both time points. Results: The exercise intervention was effective at inducing the expected improvements in aerobic fitness. Overall, the exercise group had a significantly greater decrease in mood symptoms across the intervention compared to the waitlist control group. Conclusions: The current pilot study is the first to evaluate the impact of aerobic exercise on mood in trauma-exposed young adults. An 8-week intervention significantly reduced mood symptoms in exercisers relative to waitlist controls. Our results are consistent with previous research indicating that physical activity reduced depressive symptoms in those with PTSD (Rosenbaum, Vancampfort, et al., 2015). Importantly, we extend these findings to individuals with subclinical or undiagnosed PTSD symptoms, where exercise may be an effective intervention to improve mood and manage or prevent further decline in mental health in those at risk of developing PTSD.